A Pentecostal Perspective on The Great Commission and Its Application in Gereja Bethel Indonesia - Abraham, Rubin Adi (Sekolah Tinggi Teologi Kharisma, 2023)
The Great Commission has been considered as one of the most important commands of Jesus Christ by the church. It has been passed down from the disciples to the early church fathers and so on until today. Many followers of Christ have tried to fulfill it to their best effort. However, the interpretation of such command, and therefore its implementations, in different churches throughout history, have not always been the same. Without saying that these approaches are wrong, more often than not, they are quite pragmatic and therefore they tend to become the end rather than the means to usher the ultimate vision of what Jesus’ followers ought to live. Additionally, the crucial role of the Holy Spirit is often downplayed in these missionary efforts. This paper attempts to provide a discussion in relation to the Great Commission from a Pentecostal perspective and to suggest some steps that can be applied in Gereja Bethel Indonesia (GBI) in its missionary approach as a result of this perspective. GBI was chosen as it is the largest Pentecostal Church in Indonesia.